Investigation of tick infestation on udders of beef cows and the related effects on calf survival and growth to weaning in the Mnisi tribal community - Webb, E.C. (Edward Cottington) (University of Pretoria, 2018)
Dissertation (MSc (Agric))--University of Pretoria, 2017.